Effect of the microwave radiation treatment of porous indium phosphide on spectra of radiative recombination centers - Red’ko, R.; Red’ko, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
To study the influence of microwave irradiation on a spectrum of defect states
in porous InP, we have measured the luminescence spectra within the range 0.50 to
2.04 eV at 77 K before and after short and long (up to 600 s) treatments in air in the
operation chamber of a magnetron at a frequency of 2.45 GHz and a surface power
density of 7.5 W/cm²
. We have obtained that the spectra of defects in researched samples
are essentially changed as well as the concentrations of local centers. Possible mechanisms
of observable changes in the semiconductor impurity-defect composition caused
by a microwave treatment are discussed.